2016
DOI: 10.1111/iej.12719
|View full text |Cite
|
Sign up to set email alerts
|

Capping carious exposures in adults: a randomized controlled trial investigating mineral trioxide aggregate versus calcium hydroxide

Abstract: Aim The aim of this multicentre, parallel-group randomized clinical trial was to compare the effectiveness of mineral trioxide aggregate (MTA) and a conventional calcium hydroxide liner (CH) as direct pulp capping materials in adult molars with carious pulpal exposure.Methodology Seventy adults aged 18 to 55 years were randomly allocated to two parallel arms:MTA (White ProRoot, Dentsply, Tulsa Dental, Tulsa, OK, USA) (n=33) and CH (Dycal ® , Dentsply DeTrey GmbH, Konstanz, Germany) (n=37). The teeth were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 30 publications
5
102
0
11
Order By: Relevance
“…, Kundzina et al . ). Operator skill and experience may also be an important, if not independently tested, variable determining the success of VPT.…”
Section: Consensus‐based Recommendationsmentioning
confidence: 97%
See 2 more Smart Citations
“…, Kundzina et al . ). Operator skill and experience may also be an important, if not independently tested, variable determining the success of VPT.…”
Section: Consensus‐based Recommendationsmentioning
confidence: 97%
“…, Kundzina et al . ). However, data on the carious penetration depth in these studies were not well defined (Marques et al .…”
Section: Consensus‐based Recommendationsmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent randomized clinical multicenter trial demonstrated that MTA performed better than Ca(OH) 2 (Kundzina et al . 2017 2017). Although the study contained information about the depth of the carious lesion, depth was not randomly distributed between the two materials (MTA and Ca(OH) 2 ) investigated.…”
Section: Reviewmentioning
confidence: 99%
“…[46] tooth survival was set as a primary outcome which was defined as asymptomatic tooth that responds normally to vitality testing and periapical radiographs don't show any bone rarefaction, the survival rate in MTA group was 53% while in the Calcium hydroxide group was 52%.…”
Section: Outcome Of Pulp Capping Using Either Calcium Hydroxide or Mtamentioning
confidence: 99%